Removal of Ciprofloxacin from Pharmaceutical Wastewater Using White Eggshells as Biosorbents - Bin Hammad, Maryam Khalid (2025)
A Master of Science thesis in Biomedical Engineering by Maryam Khalid Bin Hammad entitled, “Removal of Ciprofloxacin from Pharmaceutical Wastewater Using White Eggshells as Biosorbents”, submitted in July 2025. Thesis advisor is Dr. Sameer Al-Asheh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).